Geoarchaeological investigations at Siepkloof Rock Shelter, Western Cape, South Africa - Miller, Christopher E.; Goldberg, Paul; Berna, Francesco (Journal of archaeological science, 2013)
The sedimentary sequence at Diepkloof Rock Shelter formed through a complex interaction of depositional and post-depositional processes and was variously influenced by biogenic, geogenic, and anthropogenic agents. Here, we present the results of a micromorphological study of the sediments at Diepkloof, focusing in particular on the numerous anthropogenic inputs and modifications recorded within the sequence. By applying the microfacies concept, we were able to identify hearth burning and maintenance, bedding construction and burning, and surface modification by trampling as major processes that contributed to the formation of the site. The human activities recorded within the sediments show a marked change throughout the sequence, implying a shift in the use of the site over time. The present study also provides a context for evaluating other classes of artifacts and data collected from the site.
Gesehen am 25.05.2021